Національно-культурні особливості поняття кар’єризм в українській та англійскій мовах - Колеснікова, І.Є. (Культура народов Причерноморья, 2014)
У статті досліджується питання зіставного ідеографічного аналізу фразеологічної
мікросистеми на позначення кар’єризму в українській та англійській мовах. Створено схему
ідеографічної класифікації розгляданої мікросистеми з урахуванням досягнень сучасної психологічної
науки, висновків етнолінгвістичної і лінгвокультурологічної галузей лінгвістики. Проналізовано деякі
фактори, що впливають на наповнення фразеологічних мікросистем обох мов. В статье исследуются вопросы сопоставительного идеографического анализа
фразеологической микросистемы со значением карьеризма в украинском и английском языках.
Составлена схема идеографической классификации рассматриваемой микросистемы, учитывая
достижения современной психологической науки, выводов этнолингвистической и
лингвокультурологической отраслей лингвистики. Проализированы некоторые факторы, влияющие на
наполнение фразеологических микросистем в языках. The article is investigated to the study of peculiarities of the phraseological microsystem designation
of the careerism in Ukrainian and English languages. The achievements of the modern psychology,
anthropological linguistics and linguistic culturology are widely used in the research poper. Some factors that
influence on the filling of language’s semantic group are analyzed. Results are characterized by the complex
caring out ideographical description of semantic groups "Сareerism" in the Ukrainian and English languages.
Also is taking into account a structure, semantics and methods of nomination of the idioms. The given
methodology of structure and semantics design allowed to educe connection of antropological phraseology
denotations with language sphere in concepts and universals of axiology in the Ukrainian and English language
picture’s world. This methodic can be used for description of other phraseology microsystems of language.